2018
DOI: 10.1002/jcp.27960
|View full text |Cite
|
Sign up to set email alerts
|

Role of MDM2 309T>G (rs2279744) and I/D (rs3730485) polymorphisms and haplotypes in risk of papillary thyroid carcinoma, tumor stage, tumor size, and early onset of tumor: A case control study

Abstract: Murine double minute clone 2 (MDM2) protein plays an important role in the regulation of p53 tumor suppressor. Genetic polymorphisms of the MDM2 gene are the candidate variants in susceptibility to various cancers. In the present study, we aimed to investigate the possible effects of MDM2 309T>G (rs2279744) and I/D (rs3730485) polymorphisms on papillary thyroid carcinoma (PTC) susceptibility and clinical or pathological features of the disease. A case control study was carried out involving in a total of 131 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Similarly, it was reported that expression of MDM2 and MDM4 genes are affected by MDM2 rs2279744 (MDM2 309T>G) and rs3730485 (MDM2 del1518) respectively by MDM4 rs4245739 (MDM4 34091 C>A) variants, the mentioned variants being associated with increased risk for different types of cancer and higher incidence of advanced tumor stages [17][18][19][20]. In contradiction with the abovementioned results, Gansmo LB et al [21] in their study among endometrial cancer patients found that rs3730485 was in strong linkage disequilibrium (LD) with rs2279744 and the variant allele of rs3730485 was associated with reduced cancer risk among patients with the wildtype genotype for rs2279744 [21].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, it was reported that expression of MDM2 and MDM4 genes are affected by MDM2 rs2279744 (MDM2 309T>G) and rs3730485 (MDM2 del1518) respectively by MDM4 rs4245739 (MDM4 34091 C>A) variants, the mentioned variants being associated with increased risk for different types of cancer and higher incidence of advanced tumor stages [17][18][19][20]. In contradiction with the abovementioned results, Gansmo LB et al [21] in their study among endometrial cancer patients found that rs3730485 was in strong linkage disequilibrium (LD) with rs2279744 and the variant allele of rs3730485 was associated with reduced cancer risk among patients with the wildtype genotype for rs2279744 [21].…”
Section: Introductionmentioning
confidence: 79%
“…TP53 rs1042522 (TP53 Arg72Pro) was reported to affect the gene and protein function [7,8] due to the fact that the Pro amino acid of p53 protein is weaker for apoptosis induction and also for suppressing cellular transformation compared to Arg amino acid [1]. MDM2 rs2279744 (MDM2 309T>G) and rs3730485 (MDM2 del1518) and MDM4 rs4245739 (MDM4 34091 C>A) variants were reported to influence the genes activity being associated with carcinogenesis and tumor progression [17][18][19][20]. Moreover, the interaction between TP53 rs1042522 and MDM2 rs2279744 [11,13,29] and between MDM2 rs2279744 and rs3730485 [21] was reported.…”
Section: Discussionmentioning
confidence: 99%
“…The complete details of exclusion criteria have been previously described. 22 In this study, there was no marked difference between PTC cases and controls with respect to age and BMI (body mass index), sex, and race. The written informed consents were signed by all the participants in this study.…”
Section: Study Populationmentioning
confidence: 45%
“…One hundred and fifty‐five controls, who had no history of disease were enrolled. The complete details of exclusion criteria have been previously described . In this study, there was no marked difference between PTC cases and controls with respect to age and BMI (body mass index), sex, and race.…”
Section: Methodsmentioning
confidence: 68%
“…Thyroid function may be impaired when there is any defect in thyroid develop-Journal of Behavioral and Brain Science ment and thyroid hormone synthesis [2]. Papillary thyroid carcinoma (PTC) is the most common in endocrine system tumors, and its incidence has increased year by year in recent years, and it is increasingly harmful to human health [3].…”
Section: Introductionmentioning
confidence: 99%